2006
DOI: 10.1093/hmg/ddl185
|View full text |Cite
|
Sign up to set email alerts
|

In vivo function of the orphan nuclear receptor NR2E3 in establishing photoreceptor identity during mammalian retinal development

Abstract: Rod and cone photoreceptors in mammalian retina are generated from common pool(s) of neuroepithelial progenitors. NRL, CRX and NR2E3 are key transcriptional regulators that control photoreceptor differentiation. Mutations in NR2E3, a rod-specific orphan nuclear receptor, lead to loss of rods, increased density of S-cones and supernormal S-cone-mediated vision in humans. To better understand its in vivo function, NR2E3 was expressed ectopically in the Nrl-/- retina, where post-mitotic precursors fated to be rod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
124
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(129 citation statements)
references
References 60 publications
4
124
0
1
Order By: Relevance
“…However, there is a significant delay, several days in rodents, for newly born photoreceptor precursors to begin expressing the specific type of opsin and other genes that confer the mature phenotype (Watanabe and Raff, 1990;Cepko, 1996). During this lag time, the photoreceptor precursors appear to be "plastic" and can be induced to differentiate into different photoreceptor subtypes, depending on intrinsic and extrinsic regulatory factors (Nishida et al, 2003;Cheng et al, 2006;MacLaren et al, 2006;Roberts et al, 2006). The intrinsic factors mainly consist of transcription factors of homeodomain, bZIP and nuclear receptor families.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a significant delay, several days in rodents, for newly born photoreceptor precursors to begin expressing the specific type of opsin and other genes that confer the mature phenotype (Watanabe and Raff, 1990;Cepko, 1996). During this lag time, the photoreceptor precursors appear to be "plastic" and can be induced to differentiate into different photoreceptor subtypes, depending on intrinsic and extrinsic regulatory factors (Nishida et al, 2003;Cheng et al, 2006;MacLaren et al, 2006;Roberts et al, 2006). The intrinsic factors mainly consist of transcription factors of homeodomain, bZIP and nuclear receptor families.…”
Section: Introductionmentioning
confidence: 99%
“…However, a majority of photoreceptors represent a morphologically hybrid cell type expressing both rod and cone genes, providing circumstantial evidence that NR2E3 is essential to suppress cone-specific gene expression in mature rods Cheng et al, 2004;Corbo and Cepko, 2005;Peng et al, 2005]. Cone-specific gene expression is also suppressed in transgenic mice ectopically expressing NR2E3 under the control of the Crx promoter in photoreceptor precursor cells; instead of cones, nonfunctional rod-like photoreceptors are generated [Cheng et al, 2006]. With respect to Opn1sw regulation, the nuclear receptors NR1A2b (thyroid hormone receptor b2) and NR1F2 (retinoid-related orphan receptor b) probably act as additional transcriptional repressors or activators, respectively [Ng et al, 2001;Srinivas et al, 2006].…”
Section: Introductionmentioning
confidence: 99%
“…With respect to Opn1sw regulation, the nuclear receptors NR1A2b (thyroid hormone receptor b2) and NR1F2 (retinoid-related orphan receptor b) probably act as additional transcriptional repressors or activators, respectively [Ng et al, 2001;Srinivas et al, 2006]. NR2E3 acts as a transcriptional activator of several rod-specific genes, including rhodopsin [Cheng et al, , 2006Peng et al, 2005]. To achieve transcriptional regulation, NR2E3 physically interacts with the DBD of CRX [Peng et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Functional enrichment analysis of the 57 differentially expressed genes in the retina between the Red Junglefowl and domestic chickens showed that four genes (RPGR, GUCA1A, TRPM1 and PDE6B) were involved in several HPO categories including decreased central vision, congenital stationary night blindness, and abnormal ERG (Table 1). We verified the differential expression of these four genes, as well as two additional genes that are important for vision, RHO [44] and NR2E3 [45][46][47], via quantitative real-time PCR (qPCR) for retina mRNA ( Figure 3E). Differences in gene expression measured by qPCR and RNA-seq were significantly correlated ( Figure 3F).…”
Section: Differential Expression Of Psgs In the Retina Between Domestmentioning
confidence: 94%
“…The significant changes in the mRNA expression in the retina between Red Junglefowl and the domestic chickens potentially have functional consequences in vision due to their respective functions. For example, NR2E3 (photoreceptor cell-specific nuclear receptor, group E, member 3) is a vital transcriptional regulator essential for photoreceptor development and differentiation due to its capability as an activator of rod cell development and a repressor of cone development [45][46][47]. In domestic chickens, downregulation of NR2E3 expression is associated with weaker visual ability and lower optical sensitivity [3].…”
Section: Differential Expression Of Psgs In the Retina Between Domestmentioning
confidence: 99%